Photodegradation of Rhodamine B Using the Microwave/UV/H2O2: Effect of Temperature. (26th August 2013) - Ferrari, Carlo; Chen, H.; Lavezza, R.; Santinelli, C.; Longo, I.; Bramanti, E.
Abstract : The oxidative decoloration of Rhodamine B (RhB) was performed in a photochemical reactor which enables microwave (MW) and UV radiation to be applied simultaneously. We used an immersed microwave source, with no need for an oven. Controlling the temperature, MW power, and UV emission of the reactor all led to a greater overall control of the process. Due to the action of highly reactive hydroxyl radicals, the decoloration of RhB was followed online using a spectrograph. Complete decoloration occurred in four minutes, and 92% of mineralisation was obtained in 70 minutes. The experiments were performed at various temperatures (21°C, 30°C, 37°C, and 46°C), with and without hydrogen peroxide. The apparent reaction rate was used to calculate the apparent activation energy of the decoloration process: E a = 38 ± 2 kJ/mol and 40 ± 2 kJ/mol with (400 mg/L) or without hydrogen peroxide, respectively. The lack of deviation from the linear behavior of the Arrhenius plot confirms that the application of MW does not affect the E a of the process. The apparent activation energy value found was compared with the few data available in the literature, which were obtained in the absence of MW radiation and are inconsistent.